Norwegian Medical Librarians’ Views about the Future (Journal of EAHIL, 2023)
The article describe Norwegian medical librarians thoughts about trends and future developments. Results from a survey among library staff in medical and healthcare libraries in Norway in June 2022 are presented.  Digital development, teaching and research support were highly emphasised, as well as the importance of physical library space, collaboration with own institution, and the library’s impact. Furthermore, the librarians also registered their competency needs within teaching and education, first line support, open science, evidence syntheses, and in cooperation and management. Our project indicates that employees in medical and health libraries are aware of trends and competency needs. These competency needs are essential to be addressed to providers of continuing education in order to offer relevant library services.